A facile hydrothermal method to synthesize Sb2S3/Sb4O5Cl2 composites with three-dimensional spherical structures1. Issue 65 (16th July 2015) - Jiang, Qian; Yuan, Xingzhong; Wang, Hou; Chen, Xiaohong; Gu, Shansi; Liu, Yang; Wu, Zhibin; Zeng, Guangming
<x xml:space="preserve">Abstract</x> Three-dimensional spherical Sb2S3/Sb4O5Cl2 microcrystallines were synthesized for the first time via a facile hydrothermal process without any oxychlorides at 100 °C.